Inclusive education and the associated classroom challenges: The teachers’ perspective with a focus on ASD - Egberink, Georgina Sarah (University of the Witwatersrand, Johannesburg, 2025)
Inclusive education is implemented in South Africa through inclusive policies such as Education White Paper 6, as well as the Screening, Assessment, Identification and Support Policy, which were used to guide the aims and questions of this research, as well as defining its scope. Inclusive education encompasses the inclusion of learners with Autism Spectrum Disorder characteristics, which is widely misunderstood and unidentified or unaccommodated. The current research set out to underline challenges faced by teachers when including learners with Autism Spectrum Disorder characteristics in the classroom in order to highlight gaps in the education system that these learners may fall through. Online questionnaires were dispersed to gather both qualitative and quantitative data. The gathered data were analysed using Chi-squared tests to highlight trends, which was followed by a thematic analysis to underline arising themes. It was determined that challenges such as the disconnect between theoretical awareness and practical application in the classroom environment, gaps in training and minimal support, inconsistent support from school-based support teams, a lack of knowledge of Autism Spectrum Disorder, and a lack of access to special schools and a rigorous placement process were outlined as possible reasons for learners with Autism Spectrum Disorder characteristics falling through the gaps. Focus areas were identified that need to be addressed in order to minimise learners with Autism Spectrum Disorder characteristics falling through the gaps, thereby maximising the inclusion of these learners in the education system.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Education in Educational Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2026
Keywords: Inclusive Education; Autism Spectrum Disorder (ASD); Teachers’ perspective; Classroom challenges; UCTD; SDG-4: Quality education; SDG-10: Reduced inequalities